Pembelajaran Bahasa Berbantuan Komputer dalam pengajaran Bahasa Inggris bagi Anak-Anak; Sebuah Analisis Bibliometrik - Patahuddin, Patahuddin; Bancong, Hartono; Syawal, Syawal; Jusuf, Harni (Al-Lisan: Jurnal Bahasa, 2024)
Computer-assisted language Learning (CALL) is a learning method that uses computers as auxiliary media to facilitate language learning. This study aims to provide a comprehensive overview of the development of research in Computer-Assisted Language Learning (CALL) in the last five years based on the Scopus database. This quantitative study uses bibliometric analysis with the search keyword Computer-Assisted Language Learning (CALL). The results of this study highlight a significant increase in the number of articles about Computer-Assisted Language Learning (CALL) indexed by Scopus every year, starting from 142 articles in 2018 and 2023, which increased to 251. The type of publication is dominated by journal articles, followed by conference papers and reviews, and the rest in the form of books or book chapters. The largest source of publications comes from Lecture Notes in Computer Science (including the subseries Lecture Notes in Artificial Intelligence and Lecture Notes in Bioinformatics) with 29 publications. Our comprehensive analysis reveals a significant downward trend in citations from 2018 to 2023. Furthermore, based on the visualization using VOSviewer shows the use of AI technology in language teaching and the impact of digital media on language learning. The results of this study show that it is essential to continue to review and evaluate the factors influencing the dissemination and acceptance of CALL research. Moreover, it is crucial to reinforce the continuity between technological innovation and practical practice in various areas of life, thereby highlighting the real-world impact of CALL research.